Spectroscopic Studies on Copper (II) Diphenylcarbazonate Complex - F. R. Fouda, M.; Hassanein, M.; S. Amin, R. (Asian Journal of Chemistry, 2010)
Copper diphenylcarbazonate complex was prepared by shaking very dilute copper sulphate solution (10–4 M) buffered at pH≈≃6 with stoichiometric quantity of purified diphenylcarbazone in benzene. The complex was separated from benzene solution by distillation under mild reduced pressure. Measurements of X-ray diffraction, IR, electronic and mass spectra of the ligand and its Cu(II) complex together with their elemental analysis were carried out. ESR spectrum of the complex (g11 = 2.214, gx/y = 2.06 and gy/x = 2.042) was also measured. Generally, the results of IR, electronic and mass spectra revealed distinct differences between ligand and Cu(II) complex which could be related to the chelation process. Moreover, the data achieved from the combined electronic and ESR spectra results of the complex suggested that Cu2+ ion is present in an elongated octahedral coordination with orth-rhombic component superimposed, where the bonding character in the equatorial plane is more covalent than that in the axial direction (K11 = 0.65 < K1 = 0.71).